Relevansi Fungsi dan Formula di Microsoft Excel Pada Tenaga Kerja Akuntan - Dwindy Harmadani; Josephine Sudiman; Reno Fithri Meuthia; Sukartini Sukartini (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This study aims to determine the relevance of functions and formulas in Microsoft Excel on jobs related to accounting. This type of research is descriptive analytic qualitative research. The data collection method of this research is interviews. This study focuses on graduates of the Accounting Department who work in public accounting firms and in companies and often use Microsoft Excel in doing their work. The data analysis technique used is an interactive model analysis technique. Testing the validity of the data in this study includes the credibility test, transferability test, dependence test and confirmability test. The results show that the use of functions and formulas in Microsoft Excel is relevant in helping accounting graduates work effectively and efficiently. The results of the research show the use of functions and formulas, namely the Home Tab function in the form of Font, Alignment, Number, Conditional Formatting, Auto Sum, Sort & Filter and Find & Select features; The Insert Tab function uses the Chart, Pivot Table, Hyperlink and Header & Footer features; Tab Page Layout function features Page Setup and Scale to Fit; The Formula Tab functions are Basic formulas, If, Subtotal, Sum, Sumif, Vlookup, Hlookup, If Error, Max, Round, Date, Now and Concatenate; The Data Tab function is the Filter feature and the Group-Ungroup feature; The Tab View function is the Freeze-Unfreeze feature.